Zmienność szyszek jodły pospolitej ( Abies alba Mill.) – zróżnicowanie budowy powierzchni łusek nasiennych - Aniszewska, Monika; Gendek, Arkadiusz; Śliwińska, Joanna (Leśne Prace Badawcze, 2017)
This study was conducted on a batch of closed silver fir cones from Jawor Forest District and a mixture of scales from the seed extraction facility Grotniki. The scales were divided into three size classes corresponding to the bottom, middle and upper part of the cones and their area was measured with the Multi Scan Base v.18.03 software. Based on the sum of the inner and outer surface area of all scales, we then determined the total area of evaporation from the cones. In addition, the area of protruding scales was measured for differently sized scales from different parts of the cones. Previous studies have shown that the average outer surface of a closed cone, calculated as the sum of protruding scales, accounts for 10% of the outer surface of an open cone. Pictures of both scale surfaces with the internal seed bed and the external protrusions were taken using a scanning electron microscope. We noticed significant differences in dimension and shape of the channels and trichomes on the scale surface. On the inner side of the scales, we found a high diversity of trichomes of different lengths, whilst the outer side contained channels. Presumably, these characteristics affect the rate of water loss from the cones during desiccation and separation of the seed. In-depth knowledge on the evaporative surfaces of fir cones and scale structure will be helpful for optimizing the industrial processes of seed extraction.